The Effect of Coordination Between Administrative Units on The Effectiveness of Purchasing – Research and Empirical Study on The Employees of Commercial Companies - Unaizah, Saudi Arabia – - Alturki, Reem Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aims to know the degree of influence of coordination between units and administrative departments in commercial companies on the effectiveness of purchase in addition to identifying the concept, goals, the importance of coordination between administrative units, the relationship between them and between other administrative processes and identifying the dimensions of purchasing effectiveness and the impact of each dimension on achieving the company’s goals. This research is based on the descriptive analytical approach, where research and empirical study has been carried out in the references of business administration and operations that clarify the role of the coordination process between administrative units on the effectiveness of purchasing. The most important results are there is a correlation between the coordination variable and some of the dimensions of the variable of purchasing effectiveness in the commercial companies from which the sample was taken, but it is a very weak and may lack in some dimensions like the correlation between coordination and competitive advantage is absent. Most of the employees in commercial companies can work in a company that lacks administrative coordination due to their highest value is the monthly salary. The most important recommendations are work to enhance the importance of administrative coordination between administrative units in commercial companies. Recruiting coordinators who perform all the coordination processes needed by the administrative units in the commercial companies.